Impact of the COVID‐19 pandemic on pathological autopsy practices in Japan. Issue 3 (4th January 2023) - Hirata, Yuichiro; Iida, Shun; Arashiro, Takeshi; Nagasawa, Sayaka; Saitoh, Hisako; Abe, Hiroyuki; Ikemura, Masako; Makino, Yohsuke; Sawa, Rintaro; Iwase, Hirotaro; Ushiku, Tetsuo; Suzuki, Tadaki; et al.
Abstract: During the coronavirus disease 2019 (COVID‐19) pandemic, autopsies have provided valuable insights into the pathogenesis of COVID‐19. The precise effect of this pandemic on autopsy procedures in Japan, especially in instances unrelated to COVID‐19, has not yet been established. Therefore, we conducted a questionnaire survey from December 2020 to January 2021 regarding the status of pathological autopsy practices in Japan during the first year of the COVID‐19 pandemic. The questionnaire was sent to 678 medical facilities with pathologists, of which 227 responded. In cases where a confirmed diagnosis of COVID‐19 was not made at the time of autopsy, many facilities counted them as suspected COVID‐19 cases if pneumonia was suspected clinically. At around half of the sites, autopsies were prohibited for suspected COVID‐19 cases. In addition, the number of autopsies of non‐COVID‐19 cases during the pandemic period was also investigated, and a significant decrease was observed compared with the incidence in the pre‐pandemic period. The COVID‐19 pandemic has affected not only the autopsies of COVID‐19 cases but also the entire practice of pathological autopsies. It is necessary to establish a system that supports the implementation of pathological autopsy practices during the pandemic of an emerging infectious disease.